2020
DOI: 10.22605/rrh5772
|View full text |Cite
|
Sign up to set email alerts
|

Factors explaining the shortage and poor retention of qualified health workers in rural and remote areas of the Kayes, region of Mali: a qualitative study

Abstract: Introduction: Shortage of health workers is a worldwide problem but is particularly critical in sub-Saharan Africa. In Mali, the number of health workers is insufficient and their retention is low, particularly in rural and remote areas. Rural postings are Rural and Remote Health rrh.org.au

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“… Witter et al 2017 [ 7 ] Understand gender influences on the health workforce in four fragile and post-conflict contexts Mixed methods 965 Physicians, medical assistance, nurses, midwives and others 44 56 Survey, document review, in-depth interviews and key informant interviews Gender analysis framework Sierra Leone and Zimbabwe 3. Ag Ahmed et al 2020 [ 12 ] Identify and understand the factors related to shortage and poor retention of skilled health workers in rural health districts of Kayes, Mali Qualitative 46 5 Physicians 35 Nurses 6 Decision-makers 59 41 In-depth interviews Thematic analysis Mali 4. Alameddin et al 2016 [ 13 ] Soliciting and synthesizing the voice of PHC and community stakeholders on the HRH recruitment and retention strategies Qualitative 22 Policy and decision-makers 36 64 Key informant interviews Thematic analysis Lebanon 5.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Witter et al 2017 [ 7 ] Understand gender influences on the health workforce in four fragile and post-conflict contexts Mixed methods 965 Physicians, medical assistance, nurses, midwives and others 44 56 Survey, document review, in-depth interviews and key informant interviews Gender analysis framework Sierra Leone and Zimbabwe 3. Ag Ahmed et al 2020 [ 12 ] Identify and understand the factors related to shortage and poor retention of skilled health workers in rural health districts of Kayes, Mali Qualitative 46 5 Physicians 35 Nurses 6 Decision-makers 59 41 In-depth interviews Thematic analysis Mali 4. Alameddin et al 2016 [ 13 ] Soliciting and synthesizing the voice of PHC and community stakeholders on the HRH recruitment and retention strategies Qualitative 22 Policy and decision-makers 36 64 Key informant interviews Thematic analysis Lebanon 5.…”
Section: Resultsmentioning
confidence: 99%
“…Women faced strong pressure from their husbands and families to leave rural regions to re-join their husbands, bringing challenges to women’s career progress. Based on the findings, the authors suggested adopting strategies considering the social norms, such as relocating spouses of civil servants to enhance retention of married staff in rural regions [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations